2005
DOI: 10.1007/s10895-005-2524-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Gold Nanoparticle-Based DNA Detection for Microarrays

Abstract: DNA microarrays are promising tools for fast and highly parallel DNA detection by means of fluorescence or gold nanoparticle labeling. However, substrate modification with silanes (as a prerequisite for capture DNA binding) often leads to inhomogeneous surfaces and/or nonspecific binding of the labeled DNA. We examined both different substrate cleaning and activating protocols and also different blocking strategies for optimizing the procedures, especially those for nanoparticle labeling. Contact angle measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
1
32
1
Order By: Relevance
“…13,16,17 BSA has been widely used for nonspecific binding reduction in biological detection. 21,41,42 In this study, the BSA surface tailored SPIONs was shown to exhibit superior antifouling on reduction of nonspecific cellular binding based on the cell assay results ( Figure 6). BSA has been found in this study to serve two major functionalities, namely the ligand exchange for water solubilization of SPIONs and antifouling for reduction of nonspecific cellular binding.…”
Section: In Vitro Laser Scanning Confocal and Mr Imagingmentioning
confidence: 74%
“…13,16,17 BSA has been widely used for nonspecific binding reduction in biological detection. 21,41,42 In this study, the BSA surface tailored SPIONs was shown to exhibit superior antifouling on reduction of nonspecific cellular binding based on the cell assay results ( Figure 6). BSA has been found in this study to serve two major functionalities, namely the ligand exchange for water solubilization of SPIONs and antifouling for reduction of nonspecific cellular binding.…”
Section: In Vitro Laser Scanning Confocal and Mr Imagingmentioning
confidence: 74%
“…The 8.3-mm-diameter bottom of a reactor was silanized using 3-glycidoxypropyltrimethoxysilane according to [15], and then 100 mL of 1.0 Â 10 À8 mol/L Ab1 was conjugated on the silanized platform and 100 mL Ag of different concentrations were respectively bound to the Ab1 in sequence. After that, 100 mL of 3.0 Â 10 À9 mol/L biotin-Ab2 was conjugated to the Ag, yielding the immunocomplexes on the platform.…”
Section: Methodsmentioning
confidence: 99%
“…As the epoxy groups at surface of silanized platform with 3-glycidoxypropyltrimethoxysilan can be used to immobilize proteins for sandwich immunoassay [15], Ab1 can be conjugated to the silanized platform. Thus, the sandwich immunocomplexes of CEA can be fabricated on the platform through immunoreaction.…”
Section: Fabrication Of Hybrids Consisting Of Sandwichmentioning
confidence: 99%
“…Combining new capabilities for controlling particle size and composition with versatile surfacemodification approaches allows the design of opticallyencoded and chemically-encoded GNP probes. Furthermore, DNA microarrays based on GNP labeling have become promising tools for fast, highly-parallel DNA detection [115][116][117][118].…”
Section: Trends Inmentioning
confidence: 99%